Habitat associations and seasonal abundance patterns of the sea cucumber Holothuria arguinensis at Ria Formosa coastal lagoon (South Portugal) - DOMINGUEZ GODINO, JORGE ANTONIO (2020)
Sea cucumbers have an important economic value and high demand. Despite that, there is a lack of knowledge about their biology, ecology and habitat distribution patterns, which is very important for sea cucumber stock management, establishment and sizing of no-take zones, restocking actions and selection of grow-out areas. This work aimed to determine the density, abundance and habitat associations of Holothuria arguinensis for a better understanding of its distribution along the coastal lagoon Ria Formosa and to select suitable areas for grow-out. In the duration of a year, monthly visual censuses were performed in two locations at Ria Formosa along the intertidal zone. The number and length of H. arguinensis ' individuals found were registered, and the coverage of algae and seagrass was estimated. It was found that H. arguinensis was distributed along the lower intertidal zone, linked to Zostera noltii meadows on muddy and sandy bottoms. These areas showed the densest population and the largest sizes of H. arguinensis. However, during the warmer months, H. arguinensis seemed to migrate to deeper waters in the channels, to avoid exposition to high temperatures and solar/UV irradiance during low tides. Areas located in the lower intertidal zone with Z. noltii meadows on sand-muddy bottoms should be selected for H. arguinensis grow-out sites.